Pemberdayaan Perempuan untuk Kesehatan Reproduksi dan Anak Balita - emy susanti; Sutinah Sutinah; Siti Mas'udah (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2023)
The health of women and children is one of the crucial issues in achieving health development throughout the world. All of these problems must be solved immediately, mainly through community service activities by implementing science and technology that have been produced by the Team's research in recent years for the community in Wringinanom District, Gresik Regency. The purpose of this activity and the target of community service activities is to provide the following solutions; 1) provide independent registration assistance related to women's and children's reproductive health; 2) strengthening women's networks through information technology; 3) Empower PKK Health Cadres. This community service is carried out from preparation, implementation, monitoring and evaluation. The data collection method was carried out by holding a pretest and posttest. This study shows that reproductive health is not just a medical problem, but also a social and cultural problem. Not because women are guilty for not understanding and not caring about their own health conditions, but more related to their insensitive access to the situation faced by women. Therefore, joint efforts are needed to increase women's knowledge related to reproductive health and children under five to achieve the third Sustainable Development Goals, namely a healthy and prosperous life.